AWE-04 Near-Focus NBI classification of villous atrophy in suspected coeliac disease: international development and validation. (June 2019) - Gulati, Shraddha; Emmanuel, Andrew; Patel, Mehul; El-Menabawey, Tareq; Vackova, Zuzana; Pavlidis, Polychronis; Gunasingam, Nishmi; Sayer, Vivienne; Murino, Alberto; Dubois, Patrick; Neumann, Helmut; Martinek, Jan; et al.
Abstract : Introduction: There are no agreed endoscopic signs for the diagnosis of villous atrophy(VA) in coeliac disease(CD), necessitating biopsies and for both diagnosis and exclusion. Here we evaluated the role of near focus Narrow Band Imaging(NF-NBI) for the assessment of villous architecture in suspected CD with development and further validation of a novel NF-NBI classification. Methods: Patients with symptoms/investigations warranting duodenal biopsy were prospectively recruited between September 2017 to August 2018. Six paired NF-white light(NF-WLE) and NF-NBI images with biopsy (2 from the first part of the duodenum, 4 from the second) were obtained from each patient. Histopathology grading used Marsh-Oberhuber classification(M-O). Images were reviewed for quality and biopsy orientation. Separate images were used for development of the classification, training and validation steps. A modified Delphi process was performed on images and video recordings by 3 endoscopists to define NF-NBI characteristics(included if kappa>0.6). 13 blinded endoscopists(5 expert, 8 non-expert) underwent a short training module on the proposed NBI classification and evaluated paired(NF-WLE/NF-NBI) images. Results: 100 consecutive patients were recruited and n=97 completed the study (66F, 51.2±17.3 yrs). TTG positive n=17/89. Prevalence of M-O VA(3a/3b/3c) in D1 and D2 biopsies was 52/194(27%) and 70/388(18%) respectively. After image quality and biopsy orientation review; 548 paired images remained. 498 paired images developed the classification; 3 descriptors:Villous shape, vascular discrimination, crypt phenotype proposed the classification. 13 endoscopists evaluated 50 paired images each(D1:20, M-O 0:26, M-O 3a-3b:13, M-O 3c:11). Pooled diagnostic test summary statistics(%) for NF-NBI diagnosis of VA(Subtotal/total atrophy) were: Sensitivity 97.9(91.67–100), specificity 82.15(62.5–100), NPV 97.7(92.59–100) and accuracy 89.7(80–96) respectively. Mean difference in confidence using NF-NBI vs NF-WLE significantly improved when assessing the first part duodenum: The classification was further validated in histopathologically proven duodenitis(n=15) images with no features of VA using the proposed classification. Conclusion: A novel NF-NBI classification for VA had been validated to reliably diagnose VA in suspected CD amongst both expert/non-expert endoscopists using readily available equipment and required only short training supporting translation to wider practice.